Identification of the Components of the Friendship-Oriented Leadership Model - Rahmati, Mehdi; Etebarian Khorasgani, Akbar; Ebrahimzadeh Dastjerdi, Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This research focuses on identifying the components of a friendship-oriented leadership model, addressing a gap in theoretical and empirical differentiation in leadership studies. Emphasizing the evolving nature of leadership, especially in the business world, this study explores the elements contributing to effective leadership in organizational settings. Method: A qualitative research approach using Grounded Theory was employed. The population included experts in organizational behavior and university professors. Data were collected through semi-structured interviews with 20 participants, reaching theoretical saturation. Results: The study identified 72 initial codes, categorized into 8 main and 5 subcategories. These include leader strategies, positive and negative outcomes, individual abilities, follower conditions, external organizational factors, and components of friendship-oriented leadership. Positive outcomes emerged as a significant category, highlighting the importance of these leadership components. Conclusion: The research concludes that understanding and implementing a friendship-oriented leadership style is crucial for organizational success. This style is characterized by mutual and open relationships, balancing power dynamics, often overlooked in traditional leadership theories.